2021
DOI: 10.1038/s41467-021-24682-9
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the biosynthetic pathway of a hybrid polyketide-nonribosomal peptide in a metazoan

Abstract: Polyketide synthase (PKS) and nonribosomal peptide synthetase (NRPS) hybrid systems typically use complex protein-protein interactions to facilitate direct transfer of intermediates between these multimodular megaenzymes. In the canal-associated neurons (CANs) of Caenorhabditis elegans, PKS-1 and NRPS-1 produce the nemamides, the only known hybrid polyketide-nonribosomal peptides biosynthesized by animals, through a poorly understood mechanism. Here, we use genome editing and mass spectrometry to map the roles… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 50 publications
(66 reference statements)
0
5
0
Order By: Relevance
“…A recent bioinformatic survey found that at least 95% of assembly-line PKSs identified are from bacteria, while only 1% are from eukaryotes ( Nivina et al., 2019 ). Despite this small percentage, modular PKSs are found across eukaryotic lineages, including unicellular protists ( Bushkin et al., 2013 ; Ganley et al., 2017 ; John et al., 2008 ; Sasso et al., 2012 ; Zhu et al., 2002 ), nematodes ( Feng et al., 2021 ; Shou et al., 2016 ), arthropods ( Brückner et al., 2020 ; Pankewitz and Hilker, 2008 ), and even chordates ( Cooke et al., 2017 ), indicating that eukaryotic PKSs may be more phylogenetically widespread than previously assumed. One such example is PKSs from protistan lineages, including dinoflagellates, green algae, and apicomplexan parasites.…”
Section: Introductionmentioning
confidence: 87%
“…A recent bioinformatic survey found that at least 95% of assembly-line PKSs identified are from bacteria, while only 1% are from eukaryotes ( Nivina et al., 2019 ). Despite this small percentage, modular PKSs are found across eukaryotic lineages, including unicellular protists ( Bushkin et al., 2013 ; Ganley et al., 2017 ; John et al., 2008 ; Sasso et al., 2012 ; Zhu et al., 2002 ), nematodes ( Feng et al., 2021 ; Shou et al., 2016 ), arthropods ( Brückner et al., 2020 ; Pankewitz and Hilker, 2008 ), and even chordates ( Cooke et al., 2017 ), indicating that eukaryotic PKSs may be more phylogenetically widespread than previously assumed. One such example is PKSs from protistan lineages, including dinoflagellates, green algae, and apicomplexan parasites.…”
Section: Introductionmentioning
confidence: 87%
“…Our network analysis indicates the presence of over 40 euglenatide‐like metabolites within these three species, including ubiquitous examples such as 845 and 847 and others such as 849 and 1006, detected only in E. mutabilis and E. sanguinea , respectively. The broad distribution, and the multitude of family members, point to an important function for euglenatides and we searched the available genomic Euglena gracilis data for homology with the nemamide BGC [38] . However, due to the incomplete assembly, and the likely absence of gene clustering in Euglena , we did not identify a candidate BGC for euglenatide biosynthesis.…”
Section: Resultsmentioning
confidence: 99%
“…The broad distribution, and the multitude of family members, point to an important function for euglenatides and we searched the available genomic Euglena gracilis data for homology with the nemamide BGC. [38] However, due to the incomplete assembly, and the likely absence of gene clustering in Euglena, we did not identify a candidate BGC for euglenatide biosynthesis.…”
Section: A Common Biosynthetic Pathway In Euglenamentioning
confidence: 88%
“…Thus, Graeme Howe discussed computational studies of how enzymes can manipulate P-H bonds, Wen Zhu highlighted the importance and role of auxiliary FeS clusters in PqqE (a radical SAM enzyme that catalyses an unusual cross-linking reaction in PQQ biosynthesis) [32] and Yutaro Saito presented his work on novel probes for the in vivo detection of peptidase activity [33]. Other talks described the elucidation and chemical logic of biosynthetic pathways leading to the C-nucleoside formycin A (Nigel Richards) [34], and nemamides, which are novel hybrid polykeptide/non-ribosomal peptide natural products (Rebecca Butcher) [35]. Continuing this theme, Avena Ross outlined how she is employing genome analysis to identify and understand the evolutionary history of pathways leading to naturally occurring poly-pyrroles such as the tambjamines (figure 3) [36].…”
Section: Other Topicsmentioning
confidence: 99%